Studying on improving sewing process of the back pocket, the waistband of the basic Jeans - Oanh, Nguyen Kieu; Duom, Vu Thi (International Journal of Scientific Research and Management (IJSRM), 2024)
Based on the codes of the MTM time measurement method and the GSD predictability time system, the study also gave some codes to build the time standard for assembling the back pocket and the waistband according to the traditional sewing processes (TSP). Then, combined with information about modern sewing equipment and time study, the research came up with several modern sewing processes (MSP) to replace TSP. The research results showed that when processing the back pocket using the back pocket hemming machine and the automatic back pocket setter machine, the ironing stage was eliminated, time-saving up to 73.5% and decreased to 66.66% of the number of operations compared to TSP; using the Kansai waistband sewing machine in combination with the folder saved time up to 65.15%; using the belt loop attaching machine saved time up to 66.7%; using the programming machine (to attach the leather label to Jeans) saved time up to 22.7% compared to TSP.